Detecting Thermally-Induced Spinodal Decomposition with Picosecond Ultrasonics in Cast Austenitic Stainless Steels. (1st March 2023) - Al Dajani, Saleem Abdulfattah Ahmed; Dacus, Benjamin Reid; Dennett, Cody A.; Burke, M. Grace; Waldron, Lawrence; Byun, Thak Sang; Wall, James J.; Anglin, Kuba Bar-Din; Al Dajani, Omar Abdulfattah Ahmed; Krakowiak, Konrad J.; Ulm, Franz.-J.; Schwartzmann, Alan; et al.
Graphical abstract: Abstract: Destructive techniques to monitor nuclear reactor component health may not always be available during service, as they are time-consuming and often require pre-installed inspection coupons. Non-destructive evaluation (NDE) techniques can bridge this gap by rapidly identifying the state of mission-critical reactor components, via inference between NDE-measurable material properties and those of ultimate interest, such as ductility and toughness. Here, we demonstrate one such inference about the health of thermally aged cast austenitic stainless steels. Observations of surface acoustic wave peak (SAW) splitting correlate with spinodal decomposition-induced embrittlement as destructively measured by Charpy impact energy. Elastodynamic calculations and molecular dynamics simulations of the effects of spinodal decomposition on elastic moduli support that the new acoustic modes present are due to stiffening in the δ -ferrite domains. This discovery enables one to probe structure-property relationships in materials in a greatly accelerated manner, suggesting that similar inference methods can be used to determine material fitness-for-service, or to quickly uncover new structure-property relationships.